2012
DOI: 10.1889/jsid20.5.273
|View full text |Cite
|
Sign up to set email alerts
|

V‐shaped electro‐optical mode based on deformed‐helix ferroelectric liquid crystal with subwavelength pitch

Abstract: — V‐shaped electro‐optical response is shown, both theoretically and experimentally, to be an inherent property of a deformed‐helix ferroelectric liquid‐crystal cell (DHFLC) under a special choice of the applied rectangular alternating‐electric‐field waveform, frequency, and cell geometry. In contrast to other known V‐shaped ferroelectric liquid‐crystal (FLC) modes, the discovered V‐shaped switching is observed in a broadband frequency range including 1 kHz, and not at a certain characteristic frequency. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In addition, the typical response time of the DHFLC modulator based on FLC-587 is known to be around 100 µs at the phase shift equal to π [17]. So, it might be concluded that all essential prerequisites are in place for elaboration of the DHFLC spatial light modulator operating almost as the ideal axicon at the phase modulation frequency about 1 kHz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the typical response time of the DHFLC modulator based on FLC-587 is known to be around 100 µs at the phase shift equal to π [17]. So, it might be concluded that all essential prerequisites are in place for elaboration of the DHFLC spatial light modulator operating almost as the ideal axicon at the phase modulation frequency about 1 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…In short-pitch DHFLC cells, the FLC helix is characterized by a submicron helix pitch, P < 1 µm, and a relatively large tilt angle, θ > 30 • . Electro-optical response of DHFLC cells exhibits a number of peculiarities that make them useful for LC devices such as high speed spatial light modulators [12][13][14][15][16], colour-sequential liquid crystal display cells [17] and optic fiber sensors [18,19]. The effects caused by electric-field-induced distortions of the helical structure underline the mode of operation of such cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although PSBPLCs have been recently considered as an emerging display and phase modulating technology, the VADHFLC mode seems to have the advantage of higher Kerr constant supplemented with faster (around an order of magnitude) electro-optical response. Under certain conditions, the EO response of DHFLC cells can also be made hysteresis free [43]. Therefore, VADHFLCs could be used in many modern electro-optical devices.…”
Section: -5mentioning
confidence: 99%
“…[7,8] For the latter function, what is as the Step one symmetric in time with zero average; see Figure 1(a). According to our knowledge, it has not yet been done a study on Δn E behaviour of DHF chiral smectic C* cells subjected to a STAIR driving voltage, but this investigation is important from both application and fundamental point of view.…”
Section: Introductionmentioning
confidence: 99%